Evidence for disseminated tumor cells in lymphatic vessels afferent to sentinel lymph nodes in patients diagnosed with cervical cancer - Shadi Younes; Andreas M. Kaufmann; Norman Häfner; Katrin Beer; Lars Jansen; Juliane Sanft; Gita Mall; Susan Koops; Matthias Dürst; Achim Schneider (Cancer Reports, 2021)
Abstract Background In patients diagnosed with cervical cancer, the purpose of lymphadenectomy is the removal of lymph nodes for diagnosis and potential treatment of metastasized tumor cells. It is unclear if afferent lymphatic vessels harbor tumor cells and, thus, may pose additional risk for recurrence or progression if not removed. Aim In this feasibility study, we analyzed the lymphatic vessels afferent to sentinel lymph node (SLN) using a highly sensitive and specific molecular marker for cervical cancer cells. Methods and Results Twenty patients diagnosed with cervical cancer of FIGO stage IA1 to IIB2 underwent laparoscopic SLN removal. Labeling was done using patent blue and the afferent lymphatic vessels were harvested from the parametric tissue and frozen at −80°C. HPV DNA type was evaluated in the primary tumor. Lymphatic vessels afferent to the sentinel lymph nodes were analyzed for the presence of viral oncogene transcripts of the respective HPV type. In one of 18 patients, all with tumor stage ≤IBI and pN0 by conventional histopathology, HPV mRNA could be detected in two of four lymphatic vessels, whereas at least one of the lymphatic vessel biopsies of both patients with tumors ˃4 cm and pN1 status was HPV mRNA positive. No clinical correlation with recurrence after a median follow‐up of 9 years was noticed. Conclusion HPV mRNA indicative of disseminated tumor cells could be detected in lymphatic vessels. The relevance of harvesting lymphatic vessels afferent to SLN in order to increase oncologic safety will have to be investigated in a future prospective study.